2018
DOI: 10.1016/j.worlddev.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Does Institutional Quality Matter for Trade? Institutional Conditions in a Sectoral Trade Framework

Abstract: This article examines the extent to which national institutional quality affects bilateral sectoral trade flows, as well as whether the conditioning role of institutions for trade has been waxing or waning with time. Based on a new trade theory framework, we derive a sectoral gravity equation, including novel variables corresponding to the exporter's labour competitiveness levels, along with importer's price indices and sectoral incomes, and analyse industry specific bilateral trade flows of 186 countries for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(108 citation statements)
references
References 45 publications
(57 reference statements)
9
91
0
2
Order By: Relevance
“…Many studies have shown that institutional quality is positively associated with trade on an aggregate level (Álvarez, Barbero, Rodríguez-Pose, & Zofío, 2018;Anderson & Marcouiller, 2002;Francois & Manchin, 2013). Studies using different institutional indicators show positive influences on the economy.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that institutional quality is positively associated with trade on an aggregate level (Álvarez, Barbero, Rodríguez-Pose, & Zofío, 2018;Anderson & Marcouiller, 2002;Francois & Manchin, 2013). Studies using different institutional indicators show positive influences on the economy.…”
Section: Referencesmentioning
confidence: 99%
“…There are different methods to represent these six indicators. Certain bodies of literature on bilateral trade have used the six variables as separate measures (Álvarez et al, 2018;Lio & Hu, 2009;Martínez-Zarzoso & Márquez-Ramos, 2018;Méon & Weill, 2005). Other studies have constructed dummy variables based on whether the institutional measure is positive or negative (i.e., above or below the median for all countries), or by summing or averaging the scores of all six indicators into one overall measure (de Groot et al, 2004;de Groot, Linders, & Rietveld, 2005;Linders et al, 2005).…”
Section: Categories Products Includedmentioning
confidence: 99%
“…See also Chor (2009) for import subsidies in a related although not similar heterogeneous firms framework. 32 Institutional quality has proven important for trade in the gravity literature, see for example, Inmaculada, Barbero, Rodríguez-Pose, and Zofío (2018) for a recent study. 33 While all exporters enjoy the same cost savings in the model due to export promotion, the industry and general equilibrium mechanisms imply that nonexporters and the most profitable exporters earn lower profits due to export promotion.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Nunn and Trefler [15] indicate that after decomposing the institution into the formal institution, the informal institution, and policy, domestic institutional sources of comparative advantage do operate through fundamentally different channels, compared with traditional sources of comparative advantage, such as factor endowments. Another group of papers focuses on the related research at the industry level or at the firm level [17,18]. Levchenko [2] proposes a theoretical analytical framework incorporating the variation of incomplete contracts into models and concludes that institutional differences among countries are an important determinant of trade flows.…”
Section: Introductionmentioning
confidence: 99%